Pricing with the American option on the futures of stock indices to hedge the risks of price Volatilities (Analytical study in Dubai Stock Exchange) - Aljanabi , Saad Majeed; Khalaf, Sajad Yousuf (International Journal of Psychosocial Rehabilitation, 2020)
The study sample consisted of five decades of futures for a number of the trap data not listed on the Stock Exchange NASDAQ Dubai Stock Exchange for a period of (18/02/2018 until 16/03/2020 ) . And the worth mentioning that the selection of market Dubai Securities was a means and not an end, as the goal basically is to study the Iraq Stock Exchange and how it developed using these tools , but technical reasons associated with PG Yap scientific awareness needed for programs of futures options by companies on the one hand and by the dealers In the market on the other hand, this innovative hedging mechanism is not being used With it absent are the multiple advantages that can be brought by all parties, which start with the interests of the investor and how to hedge against the losses that may be caused to him, and by using a number of financial and statistical methods using a program EXCEL And ( spss ) In order to analyze the study variables and test their hypotheses, the study reached a number of conclusions, perhaps the most important of them (the results of financial and statistical analysis to study future options to hedge against stock price fluctuations have proven that changes in future contract indicators in the case of purchase options that most contracts are directly proportional, i.e. within the possibility of achieving Profit either in the case of selling options, that the majority of contracts are proportional to the inverse proportion, i.e. within the possibility of making a profit as well. ) ,. Accordingly, the study came out with a number of recommendations, perhaps the most important of which is the necessity to rely on (the use of hedging options on the future to achieve returns and avoid losses using the model) Barone & Whaley)